Use of the prostate health index in the detection of prostate cancer at all PSA levels (use of prostate health index in prostate cancer). Issue 4 (20th December 2020) - Akdogan, Nebil; Aridogan, I. Atilla; Izol, Volkan; Deger, Mutlu; Gokalp, Fatih; Bayazit, Yildirim; Tansug, M. Zuhtu
Abstract: Objectives: To determine the efficiency of prostate health index (PHI) calculated simultaneously during an ultrasound‐guided fine‐needle prostate biopsy in prostate cancer diagnosis. Methods: The present study included 258 subsequent patients who underwent a TRUS‐guided biopsy in our clinic between August 2015 and March 2016 due to elevated blood levels of PSA and suspicion of prostate cancer. The total PSA, free PSA and pro‐PSA were analysed in all patients before the procedure. Results: The average age of 258 patients was 63.5 (36‐91) years, and the mean PSA level and mean PHI values were 40.1 (0.12‐2170) and 118 (0.41‐1308), respectively. According to the PSA data, the patients were divided into two groups: the low PSA (<4 ng/mL) group containing ten patients with adenocancer (31.2%) and 22 patients with BPH (68.8%) and the high PSA (>4 ng/mL) group consisting of 86 patients with adenocancer (42.2%) and 118 (57.8%) with BPH. The sensitivity and specificity of PSA in detecting prostate adenocancer were calculated as 89.6% and 15.7%, respectively. Similarly, when a PHI level below 55 was accepted as low, and a PHI level at or above 55 was accepted as high, PHI's sensitivity and specificity were determined as 71.9% and 67.9%, respectively. Conclusions: The overall findings indicate that the specificity of PHI is higher than PSA in terms of prostate cancer detection.